A two-stage method for determining the position and corresponding precision of marine mammal sounds - Simons, Dick G.; Van Moll, Camiel; Snellen, Mirjam (Canadian Acoustics, 2004)
Today there is a concern that man-made sounds, such as that from sonar experiments, seismic operations and oil rigs, affect marine mammals. Detection and localisation of marine mammals will definitely support measures to reduce the possible detrimental effects. This paper presents a two-stage localisation method, which is applied to data collected with an array of five hydrophones moored to the seabed in the Bay of Fundy, Canada. The array forms a 14 by 14 km square with one hydrophone in the centre. The method makes use of the relative travel times of the mammal's sound to the four hydrophones at the square vertices with respect to the travel time to the central hydrophone. First, a good initial position is obtained using hyperbolic fixing. In the second step the solution is improved in an iterative process, where each iteration determines the least-squares solution of the set of four linearized equations for the measured relative travel times. Calculating the error ellipse from the covariance matrix of the solution provides the localisation accuracy. There are several parameters that affect the source position accuracy. These include the uncertainties in arrival times, sound speed and receiver positions. Their effect on the localisation accuracy is assessed.